A case of dedifferentiated chondrosarcoma arising in the cricoid cartilage that mimicked an aneurysmal bone cyst. Issue 2 (17th February 2018) - Chen, Lixiao; Yu, Ziwei; Jiang, Rui; Dong, Pin; Shen, Bin; Li, Yu
ABSTRACT: Dedifferentiated chondrosarcoma of the larynx is a rare and highly malignant tumor. We present the report of a 59-year-old man with dedifferentiated laryngeal chondrosarcoma, which was difficult to diagnose even under microscopic examination. The original diagnosis was an aneurysmal bone cyst, and the final diagnosis was established only after careful consideration of the imaging, surgical, and microscopic findings. In clinical practice, there are many similarities between dedifferentiated chondrosarcoma and aneurysmal bone cysts. Furthermore, it is difficult to identify dedifferentiated laryngeal chondrosarcoma with a giant-cell malignant mesenchymal component. This report describes our experience and discusses this phenomenon.